2019
DOI: 10.1016/j.ajic.2019.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary analysis of the antimicrobial activity of a postoperative wound dressing containing chlorhexidine gluconate against methicillin-resistant Staphylococcus aureus in an in vivo porcine incisional wound model

Abstract: Background: Surgical site infection is a major postoperative complication after surgical procedures. The effectiveness of postoperative antimicrobial dressings in reducing surgical site infections is unclear and limited information is available on the efficacy of chlorhexidine gluconate (CHG)-impregnated postoperative dressings. Methods: A pilot study was conducted to examine the efficacy of an innovative CHG-impregnated postoperative dressing in reducing the burden of methicillin-resistant Staphylococcus aure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 34 publications
0
4
0
2
Order By: Relevance
“…Furthermore, alginate and other polymeric hydrogels-based wound dressings have also shown effectiveness in managing surgical incisions [ 316 , 317 ]. In another study, chlorhexidine gluconate (CHG) film-based antimicrobial wound dressings have shown effectiveness with strong antimicrobial activity and wound healing properties in post-operative wounds in the porcine incisional wound model [ 318 ].…”
Section: In Vivo Methods For Evaluation Of Wound Dressing Materialsmentioning
confidence: 99%
“…Furthermore, alginate and other polymeric hydrogels-based wound dressings have also shown effectiveness in managing surgical incisions [ 316 , 317 ]. In another study, chlorhexidine gluconate (CHG) film-based antimicrobial wound dressings have shown effectiveness with strong antimicrobial activity and wound healing properties in post-operative wounds in the porcine incisional wound model [ 318 ].…”
Section: In Vivo Methods For Evaluation Of Wound Dressing Materialsmentioning
confidence: 99%
“…Regarding CHG, its efficacy in reducing MRSA contamination in surgical wounds has been previously tested in a porcine model, demonstrating significant antimicrobial activity and emphasizing the potential of CHG dressings against MRSA [37]. Furthermore, meta-analyses support this by stating that dressings impregnated with CHG significantly reduce infections related to central venous catheters, with rare adverse effects [38,39].…”
Section: Discussionmentioning
confidence: 95%
“…CD and bacitracin are widely used as wound dressings and in topical treatment. However, they fail to completely decontaminate S. aureus -infected wounds [ 36 ], in addition to their associated cytotoxicity that might interfere with the healing process [ 37 ]. We showed that combination of non-antibiotic agents including antiseptics with bacitracin successfully upgraded their capacity to kill planktonic S. aureus (although the results are unpublished).…”
Section: Discussionmentioning
confidence: 99%